A family of no prominence : the descendants of Pak Tŏkhwa and the birth of modern Korea - Park, Eugene Y. (Stanford University Press, 2014)
Koreans are known for their keen interest in genealogy and inherited ancestral status. Yet today's ordinary Korean would be hard pressed to explain the whereabouts of ancestors before the twentieth century. With A Family of No Prominence, Eugene Y. Park gives us a remarkable account of a nonelite family, that of Pak Tokhwa and his descendants (which includes the author). Spanning the early modern and modern eras over three centuries (1590-1945), this narrative of one family of the chungin class of people is a landmark achievement. What we do know of the chungin.